Reducing health inequalities: the use of Health Impact Assessment on Rural Areas - Elvira Sanz Tolosana (Universidade de São Paulo, 2015)
Health is greatly influenced by social, economic and political determinants. Accordingly, decisions influencing people's health do not concern only health services or 'health policies', but decisions in many different policy areas have their influence on these health determinants. Health Impact assessment (HIA) is a predictive tool to support decisions in policy-making. The ultimate goal of this framework is to maximize health gains and, as far as possible, to reduce health inequalities. HIA presents a commitment to ensure that the rural dimension is routinely considered as part of the making and implementing of policy. The aim of this paper is to review the use of HIA on rural areas. Conclusions: HIA shows its great potential to contribute to local authority decision making. The use of HIA was identified in 2 key areas: strategic planning (sustainable development, EU Common Agricultural Policy, Federal Farm Bill, land-use planning work); and in specific smaller scale projects (rural health service redesign proposal, accessing healthy food, transport, health care disparities, etc.).